(untitled) (UNED Research Journal, 2016)
Ecosystems provide various environmental services such as key recharge and ow of the water resource, but they can be damaged by human activity. Understanding vegetation cover allows administrators to predict the effects of such changes on groundwater and the actions needed in ad- ministration. Grecia Forest Reserve is a 2000-hectare zone in Costa Rica that affects eleven settlements in the region. There we measured vegetation cover and water volume in all water springs (N=70). We identified four vegetation groups: secondary forest, scrubland, pasture and pine forest; and an overall mean ow of 1,12 l/s/ha. Most water springs were found in secondary forest, which had the highest vegetation cover; however, scrublands had higher flows.